PENGARUH PARTISIPASI PENGANGGARAN, JOB RELEVANT INFORMATION, KEJELASAN SASARAN ANGGARAN, DAN KAPASITAS INDIVIDU PADA SENJANGAN ANGGARAN - Tri Pradani, Komang Kartika; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2016)
This study aims to provide empirical evidence of the effect of budget participation, job relevant information, budget goal clarity and capacity of the individual to the emergence of budgetary slack. This study was conducted on 54 SKPD Badung data collection method using questionnaire and interview techniques. The number of respondents who used as many as 218 people by using purposive sampling method. The analysis technique used in this research is multiple linear regression. The results showed a positive effect of participation budgeting on budgetary slack, while job relevant information, budget goal clarity and individual capacities negative effect on budgetary slack.
Keywords: Participation Budgeting, Job Relevant Information, Budget Targets Clarity, Individual Capacity, Budgetary Slack